Financing Sustainable Development: Actors, interests, politics - Adam Moe Fejerskov; Mikkel Funder; Lars Engberg-Pedersen; Yang Jiang; Helle Munk Ravnborg; Neil Webster (Danish Institute for International Studies (DIIS), 2016)
The Sustainable Development Goals (SDG's) represent the most ambitious global development agenda in history. Achieving them will require financing far beyond traditional aid, especially at a time where established donors are cutting or diverting aid budgets to meet refugee and security issues. Alternative sources of development financing seem ever more critical, such as the private sector, private foundations and the BRICS. But what are in fact the interests and modes of operation of these actors, and to what extent do they align with the aims of the SDGs? And how do national governments of developing countries themselves perceive and approach these new sources of financing? In this new report, six DIIS researchers examine the policies, mind-sets and interests of some of the many actors that will be playing a fundamental role in the complex and challenging task of financing sustainable development in the years to come.
Keywords: 300